The Influence of Financial Distress and Profitability on Audit Report Lag in Consumer Cylicals Sector Company Listed on the Indonesia Stock Exchange in 2020-2022 - Sihombing, Tanggor; Azzahra, Vega Yulia (Universitas Pelita Harapan, 2024)
This study aims to examining the effect of Financial Distress and Profitability on Audit Report Lag in companies operating in the Consumer Cyclicals sector listed on the Indonesia Stock Exchange and S&P Capital IQ platform. The independent variables used in this study are Financial Distress and Profitability. The dependent variable in this study is Audit Report Lag. The sample collected and used in this study is secondary data from the financial statements of Consumer Cyclicals companies available on the official website of the IDX from 2020–2022. The technique for collecting samples was using the purposive sampling method and analyzed using the multiple regression method with a total sample of 276 data using STATA software. The results of this study indicate that Financial Distress has a positive effect on Audit Report Lag and Profitability has no effect on Audit Report Lag in Consumer Cyclicals companies listed on the IDX during 2020–2022.